A case study of industry–academia communication in a joint software engineering research project. Issue 10 (29th July 2021) - Rico, Sergio; Bjarnason, Elizabeth; Engström, Emelie; Höst, Martin; Runeson, Per
Abstract: Empirical software engineering research relies on good communication with industrial partners. Conducting joint research both requires and contributes to bridging the communication gap between industry and academia (IA) in software engineering. This study aims to explore communication between the two parties in such a setting. To better understand what facilitates good IA communication and what project outcomes such communication promotes, we performed a case study, in the context of a long‐term IA joint project, followed by a validating survey among practitioners and researchers with experience of working in similar settings. We identified five facilitators of IA communication and nine project outcomes related to this communication. The facilitators concern the relevance of the research, practitioners' attitude and involvement in research, frequency of communication and longevity of the collaboration. The project outcomes promoted by this communication include, for researchers, changes in teaching and new scientific venues, and for practitioners, increased awareness, changes to practice, and new tools and source code. Besides, both parties gain new knowledge and develop social‐networks through IA communication. Our study presents empirically based insights that can provide advise on how to improve communication in IA research projects and thus the co‐creation of software engineering knowledge that is anchored in both practice and research. Abstract : Empirical software engineering research relies on good communication with industrial partners. We performed a case study in the context of a long‐term industry‐academia joint project. We identified five facilitators of industry‐academia communication and nine project outcomes promoted by that communication. Our study presents empirically based insights that can provide advise on how to improve communication in joint research.